Is Sustainable Banking Initiative Good Business for the Banks? A Comparative Pre and Post Adoption Study - Nwaigwe, Nwakanma Godwin; Matemane, Reon (Journal of Ecohumanism, 2024)
This paper contributes to the business case for sustainable development literature by examining whether sustainable banking (SB) initiatives translate to good business for the banks. To achieve this, we analyzed the link between SB and certain bank performance (BP) indicators, and examined if significant difference exists in BP between the pre and post-Nigeria sustainable banking principles (NSBP) adoption periods. The study was based on 12 deposit taking banks listed on the Nigerian Exchange Group (NGX) studied for18 years (2005 to 2022), divided into two equal periods of pre and post-NSBP adoption. The empirical results support the assertion that a positive difference exists in BP between the pre and post NSBP adoption periods, with the difference in profitability indicators increasing in significance over time. The findings have managerial implication for the banks, such that to chart a sustainable growth path for the banks, looking beyond short-term impact of sustainable actions is key.